College Student Competition Recommendation and Development Planning Prediction Platform Based on BP Neural Network Algorithm. (October 2019) - Huang, Fulin; Zheng, Zejun; Jiang, Xuenan; Chen, Jiayi; Liu, Yi; Yang, Qiulong
Abstract: With the development of today's society, the number of college students in China has steadily increased, and the number of college students is increasing. More and more college students choose to participate in competitions to improve their abilities. Therefore, our team has integrated the relevant competition resources of major universities and established a competition system with high efficiency, real-time interaction and high communication for the purpose of college students. The ordinary users are college students. In addition to registration, briefing, mutual help discussion forum and video broadcast of the event, the platform also provides users with professional classification based recommendation, college student development planning prediction, live broadcast, teammate recommendation, Special services such as rapid team formation, fast pipeline, experience sharing and authoritative guidance improve the user experience while simplifying the registration process. Form a unique platform for college students.